2014
DOI: 10.5006/1170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alloying Elements on Crevice Corrosion Inhibition of Nickel-Chromium-Molybdenum-Tungsten Alloys Under Aggressive Conditions: An Electrochemical Study

Abstract: The effects of Cr, Mo, and W on the crevice corrosion of a number of commercial Ni-Cr-Mo(W) alloys in 1.0 mol/L sodium chloride (NaCl) were studied using the potentiodynamicgalvanostatic-potentiodynamic technique to measure film breakdown and repassivation potentials as well as protection temperatures. As expected, Cr is the key element determining resistance to crevice initiation, but a substantial Mo alloy content is required to achieve maximum film stability, especially at temperatures >60°C. Mo, not Cr, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 26 publications
1
50
1
Order By: Relevance
“…The results presented herein suggest that W in solid solution plays a decisive role in increasing localized corrosion resistance when added to SDSS at about 2.2 wt%. Moreover, the higher CCRT measured by CPP on creviced samples also suggested that W additions led to a faster repassivation kinetics than that of low-W or W-free SDSS, results that are in line with the effect of W additions to Ni-based alloys [83][84][85]. Adding W to the PRE formula as detailed by ISO 21457 5 translates to a PREN,W of 43.87(Table 3), similar to that of super austenitic stainless steel grades containing 6 wt% Mo (e.g., UNS S31254).75 The results of this investigation clearly indicated that UNS S39274 has a localized corrosion resistance equivalent to that of stainless steels containing higher amounts of Cr and Mo.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The results presented herein suggest that W in solid solution plays a decisive role in increasing localized corrosion resistance when added to SDSS at about 2.2 wt%. Moreover, the higher CCRT measured by CPP on creviced samples also suggested that W additions led to a faster repassivation kinetics than that of low-W or W-free SDSS, results that are in line with the effect of W additions to Ni-based alloys [83][84][85]. Adding W to the PRE formula as detailed by ISO 21457 5 translates to a PREN,W of 43.87(Table 3), similar to that of super austenitic stainless steel grades containing 6 wt% Mo (e.g., UNS S31254).75 The results of this investigation clearly indicated that UNS S39274 has a localized corrosion resistance equivalent to that of stainless steels containing higher amounts of Cr and Mo.…”
supporting
confidence: 59%
“…It is important to emphasize that the parametric PRE definition proposed herein exclusively applies to SDSS. In Ni-based alloys, where the beneficial effects of W have been broadly recognized,[83][84][85] there shall be no limitation on the W content allowed in the PREN,W…”
mentioning
confidence: 99%
“…The chemical composition for these alloys is shown in Table VIII As shown in Figure 16, the calculated pH values of 625, C-276, C-22, and G3 decrease as the molality of the solution increases. Using the pH of the 4.0 m solution as a reference and the general trend that crevice corrosion resistance increases in the order G3 < 625 < C22 < C276, 7,24 there does not appear to be a correlation between crevice corrosion susceptibility and critical crevice solution pH. On the contrary, from the trend in pH in Figure 16, one might predict that G3 would be the most resistant to crevice corrosion.…”
Section: Discussionmentioning
confidence: 98%
“…6 Other studied nickel-based CRAs include the recently developed alloys C-22HS (UNS N07022), HYBRID-BC1 (UNS N10362), 59 (UNS N06059), C-2000 (UNS N06200), etc. [16][17][18][19] Selection of a nickel-based alloy as the material for the corrosion-resistant layer of waste containers for saturated and unsaturated repositories has distinct advantages relative to other metals/alloys: 20,21 • The expected containment is very long, synonymous with low corrosion rates.…”
mentioning
confidence: 99%
“…2, as a function of the weight percentages of Cr, Mo and W. [16][17][18] The crevice corrosion resistance of Ni-Cr-Mo and Ni-Cr-Fe alloys generally increases with PRE, though there are some examples of changes in the alloy ranking depending on environmental conditions. 32 Even though there is some criticism on the use of PRE, it is widely used as a rough indication of the localised corrosion resistance of nickel-based alloys and stainless steels.…”
mentioning
confidence: 99%